0668 The Effect of Antidepressant Medications on Sleep Architecture in a Primarily Middle-aged Sample of Women with Multi-morbidities: Chronic Insomnia, Chronic Pain, and Depression. (25th May 2022) - Sparrow, Emilie; Stearns, Melanie; Nair, Neetu; McCrae, Christina
Abstract: Introduction: Depression commonly impacts sleep architecture by increasing REM and decreasing stage 3 sleep. Growing evidence suggests antidepressants may reduce or reverse those effects in depressed individuals but has largely ignored their impact in the context of multi-morbidities. Depression, chronic insomnia, and chronic pain are common in middle-aged women and are thought to share a common neurobiological basis. They often co-occur, and thus, represent a common multi-morbidity triad. Here we examine whether %REM and %stage 3 sleep differ as a function of antidepressant use (yes/no) in a primarily middle-aged sample of women with all three morbidities. Methods: Female adults (18+ years, n=91, Mage=51, SD=10.16) with comorbid insomnia, chronic pain, and depression (≥17 BDI-II score) completed one night of ambulatory polysomnography and reported antidepressant medication use (yes/no) and type (SSRI/SNRI/SARI/TCA/NDRI) as part of baseline data collection for a RCT (SPIN, NCT02688569). ANCOVA (R v4.1.1) examined group differences (antidepressant use: yes/no) in %REM and %stage3 sleep, controlling for age and sleep medication use. Results: Only %REM was significantly lower (F=6.213, p=.015) in antidepressant users (n=48, M=14.85, SD=9.38) versus non-users (n=43, M=19.23, SD=6.70). An exploratory follow-up ANCOVA examined whether antidepressant type was important. Two groups were formed based on antidepressant mechanism of action (medications affecting serotonin, i.e., SSRI/SNRI/SARI vs medications affecting other neurotransmitters, i.e., TCA/NDRI), and their means were compared. Only %stage3 sleep was significantly lower (F=7.937, p=.007) in SSRI/SNRI/SARI users (n=37, M=11.18, SD=9.28) versus TCA/NDRI users (n=11, M=19.36, SD=13.04). Conclusion: Thus, general antidepressant medication use may help decrease REM, but the increase of stage 3 sleep depended on which medications were used (i.e., TCA/NDRI). These findings suggest a neurophysiological functioning difference between types of antidepressants, particularly for this population of women with chronic pain, insomnia, and depression. This difference may be due to SSRI/SNRI/SARIs impacting serotonin, which may have an impact on REM, but not stage 3 sleep. However, the current study only had a small group of people using TCA/NDRIs, limiting generalizability and inferences. Future longitudinal research with a larger sample size is needed to parse out the effects of each antidepressant medication type individually and over time. Support (If Any): ClinicalTrials-NCT02688569, PI McCrae.